Peranan Perceived Peer Pressure dan Search for Meaning terhadap Academic Resilience Mahasiswa di Surabaya - Jesslyn, Anastasia; Yuliawati, Livia; Eunike, Prisca (Personifikasi: Jurnal Ilmu Psikologi, 2024)
Academic resilience is an important factor for university students to navigate through their assignments, as the absence of quality may cause issues. Perceived peer pressure and search for meaning act as major predictors of academic resilience as both factors are crucial for university students. This research aims to identify the roles of perceived peer pressure and search for meaning on academic resilience in university students in Surabaya. This research is a quantitative study using a survey design and double regression data analysis technique. The sample of this study are active university students in Surabaya with the number of 208 respondents collected through accidental sampling in the form of non-probability sampling. Measuring instruments used in this research are The Academic Resilience Scale (ARS-30) (Alpha Cronbach 0,685 (perseverance), 0,861 (reflecting and adaptive help-seeking) and 0,761 (negative affect and emotional response)), Perceived Peer Pressure Scale (Alpha Cronbach 0,865 (yielding to peer pressure), 0,844 (resistance to peer pressure), dan 0,633 (peers encouragement)) and Meaning in Life Questionnaire (MLQ) (Alpha Cronbach 0,922). When juxtaposed, this research finds a significant role of perceived peer pressure on academic resilience while no role of search for meaning is found. On the other hand, search for meaning is found to have an independent role on academic resilience. Thus, it is concluded that perceived peer pressure has a more dominant role in comparison to search for meaning. Further research needs to be done regarding search for meaning as the mediator of the roles of perceived peer pressure on academic resilience.